A New Tool for Assessing Workforce Management Policies Over Time - Asch, Beth J.; Mattock, Michael G.; Hosek, James (RAND Corporation, 2023)
This research extends the dynamic retention model to simulate the transition to the steady state, providing researchers with the ability to assess the effects of workforce management policies both in the steady state and in the transition to the steady state as well as to assess the effects of alternative implementation strategies. It helps policymakers better understand workforce dynamics and how they respond to policy change.